2021
DOI: 10.1186/s12920-021-00942-x
|View full text |Cite
|
Sign up to set email alerts
|

New susceptibility alleles associated with severe coronary artery stenosis in the Lebanese population

Abstract: Background Coronary Artery Disease (CAD) is the narrowing or blockage of the coronary arteries. It is closely associated with numerous genetics and environmental factors that have been extensively evaluated in various populations. In recent studies, severe phenotypes have been strongly linked to genetic risk factors. Methods This study investigated the association of clinical, demographic, and genetic factors with severe coronary artery stenosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For this reason, different studies published updates concerning CVDs’ prognosis and treatment in the era of COVID-19. For instance, observational studies investigated the association of clinical, demographic, and genetic factors with severe coronary artery stenosis phenotypes, namely hyperlipidemia 86 , 87 while another narrative review reported the accuracy of a new intravascular optical coherence tomography in the evaluation of stent implantation and post-stent tissue coverage. 88 Moreover, one published study documented the in-hospital discharge trends for patients with acute heart failure and highlighted the need for enlisting complete education as part of the discharge process, in addition to abidance to the guidelines in prescribing medication 89 while another study summarized common etiologies for post-orthostatic tachycardia syndrome such as infections, especially viral, pregnancy, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, different studies published updates concerning CVDs’ prognosis and treatment in the era of COVID-19. For instance, observational studies investigated the association of clinical, demographic, and genetic factors with severe coronary artery stenosis phenotypes, namely hyperlipidemia 86 , 87 while another narrative review reported the accuracy of a new intravascular optical coherence tomography in the evaluation of stent implantation and post-stent tissue coverage. 88 Moreover, one published study documented the in-hospital discharge trends for patients with acute heart failure and highlighted the need for enlisting complete education as part of the discharge process, in addition to abidance to the guidelines in prescribing medication 89 while another study summarized common etiologies for post-orthostatic tachycardia syndrome such as infections, especially viral, pregnancy, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, a GWAS studies suggested that the PCSK6 snps are linked to blood lipid metabolism and in ammatory [28]. What's more an recent research found PCSK6 snps were signi cantly associated with severe coronary artery stenosis [32].The analysis of expression quantitative trait loci (eQTL) showed the rs20543 snps were associated with expression of PCSK6 in single tissue (Fig. 1a), and the carriers with rsrs20543 GG increased expression of PCSK6 in Brian-caudate.…”
Section: Discussionmentioning
confidence: 98%
“… 27 Among the study population, 1394 patients from Stenosis Group, and 705 patients from Stenosis Group had genotyped data available and were included in the genetic association using PLINK. 28 Using PLINK, quality control (QC) was applied, and variants were filtered out. Sex checks were performed using PLINK and variants were excluded for having >5% missing genotyping rates and <1% MAF (minor allele frequency), and for failing HWE (Hardy-Weinberg Equilibrium) test (P > 0.05).…”
Section: Methodsmentioning
confidence: 99%